A ambientalização na prática pedagógica: contextos urbanos, sentidos atribuídos e possibilidades da educação ambiental crítica. - Soares, Márcia Belo (2020)
Taking the Environmental Education (EE) as an inclusive, permanent and continued educational practice, which must be present - in accordance with the National Policy on Environmental Education - in all teaching levels and methods; being also present in the Municipal Policy on Environmental Education from Santo André and integrated with the Political Pedagogical Projects (PPPs) from Municipal Education Institutions; this research has as its main goal to analyse how the Critical Environmental Education is being discussed at schools from Santo André. For such study a research has been carried out in order to investigate the EE presence in PPP, by getting to know them as well as analysing the epistemological and theoretical school curriculum in relation to teaching practices on EE. The qualitative research, based upon a Case Study, was carried out with 8 Municipal Schools, as follows: 4 schools located in the Environmental Protection Area (EPA) and 4 schools located in the Urban Area (UA); involving 41 educators. The research was conducted by collecting data from different sources as bibliographic and documental research from Political Pedagogical Projects (PPPs); questionnaires (41 Educators); semistructured interviews (11 Educators) and a non-participant observation on pedagogical practices developed by two schools (1 located in the EPA and 1 located in the UA). In order to analyse and to interpret the PPP data and the non-participant observation on pedagogical practices, the research took into account guidelines defined by researchers from REDE ACES (Greening Curriculum in Higher Education). In relation to the interviews, it has been used the Content Analysis Technique. The PPP from the UA (260) as well as the ones from the EPA (168) have shown evidences which indicate that the environmental theme is dealt in a category entitled as “with greening potential”; in which such topic appears in a simple and non-detailed way, or just taking into consideration the ecological approach. The educators concepts and the pedagogical practices are geared towards a naturalistic view. The research results showed that the EE conception within the Municipal School System of Santo André is grounded upon the traditional view, geared towards the environment preservation and conservation. The outcomes led to the conclusion that the insertion of the environmental theme in law represents a historic achievement. However, the insertion in law - by itself - does not solve the environmental problem; it is necessary to take a step ahead the naturalistic view. For such purpose, everyone should be involved in the debate with the intention of reaching solutions as a team; thus moving towards to a more critical, transforming and emancipatory EE. In this respect, the inclusion of a Greening Curriculum in the PPPs is a way to be followed towards to a more critical EE.